Tinjauan Pengaruh Alat Pencetakan Tahu Terhadap Produktifitas Tahu Di Desa Waegeren Kabupaten Buru - Muhammad Bula; Ilyas Wali (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
The problem described in this study is how much tofu production is produced, the value of depreciation of equipment and income of tofu craftsmen Waegeren Village Buru Regency in producing tofu using modern tofu printing equipment technology. From the problems outlined, in the goel the goalto be archived is know the level of tofu production produced by tofu craftsmen Waegeren Village Buru District every day, knowing the value of depreciation of tofu printing equipment each month based on economic analysis theory, and knowing the amount of tofu craftsman income each month. The research method uses the method of observation, which is a method of research carried out without any intervention at all from the researchers, the researchers conducted observations and interviews at the tofu industry craftsman in Waegeren Village. The results obtained, tofu production using modern technology by tofu craftsmen Waegeren Village Buru Regency per day only reached 150 kg or equivalent to 225 pieces of tofu. Meanwhile, the cost of equipment depreciation and tofu craftsman income every month is Rp. 45,900,000 and Rp. 9,855,000.